Hapln2 in Neurological Diseases and Its Potential as Therapeutic Target - Wang, Qinqin; Wang, Chunmei; Ji, Bingyuan; Zhou, Jiawei; Yang, Chunqing; Chen, Jing (Frontiers in Aging Neuroscience, 2019)
The hyaluronan and proteoglycan binding link protein 2 (Hapln2) is known to be crucial for the maintenance of the binding of chondroitin sulfate proteoglycans to hyaluronan. Hapln2 deficiency led to abnormal expression of extracellular matrix proteins and dysfunction of neuronal conductivity, indicating the vital role of Hapln2 in extracellular matrix formation and neuronal conductivity. Study has demonstrated that Hapln2 promoted to the aggregates formation of α-synuclein, contributing to the neurodegeneration of Parkinson’s disease. Recent research showed Hapln2 was present in the intracellular neurofibrillary tangles. Besides, the expression levels of Hapln2 decreased significantly in Schizophrenia anterior temporal lobe compared to the healthy subjects. All of these evidences suggested the involvement of Hapln2 in neurological diseases, indicating the potential roles of Hapln2 in pathological processes of central nervous system disorders. A better understanding of the function of Hapln2 in the central nervous system will provide new insights into the molecular mechanisms of these diseases and be helpful for establishing promising therapeutic strategies for brain disorders. Herein, we review recent progresses about the role of Hapln2 in physiology and pathology of brain.